A Dual-Responsive Peptide-Based Smart Biointerface with Biomimetic Adhesive Behaviors for Bacterial Isolation - Wang, Fenghua (Langmuir : the ACS journal of surfaces and colloids, 2021)
As mimics of the extracellular matrix, surfaces with the capability of capturing and releasing specific cells in a smart and controllable way play an important role in bacterial isolation. In this work, we fabricated a dual-responsive smart biointerface via peptide self-assembly and reversible covalent chemistry biomimetic adhesion behavior for bacterial isolation. Compared with that of the biointerface based on a single reversible covalent bond, the bacterial enrichment efficiency obtained in this work was 2.3 times higher. Furthermore, the release of bacteria from the surface could be achieved by dual responsiveness (sugar and enzyme), which makes the biointerface more adaptable and compatible under different conditions. Finally, the reusability of the biointerface was verified via peptide self-assembly and the regenerated smart biointerface still showed good bacterial capture stability and excellent release efficiency, which was highly anticipated to be more widely applied in biomaterial science and biomedicine in the future